A physical sunscreen slurry and its preparation method and application

Through reasonable preparation and process processing, the problem of easy agglomeration of sunscreen particles in physical sunscreen slurry is solved, and a physical sunscreen slurry with high dispersion, long-term stability and low viscosity is achieved, improving the sun protection effect and skin feeling of sunscreen products.

CN119745704APending Publication Date: 2025-04-04SHANGHAI JIYAN BIO PHARM CO LTD +2

Patent Information

Application Number
CN202510006724.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

During the preparation process, the existing physical sunscreen slurry is lipophilic and high surface energy of titanium dioxide and zinc oxide, which leads to the agglomeration of sunscreen particles, which has poor dispersion and stability, which affects the sunscreen effect and false whitening phenomenon.

Method used

By reasonably preparing physical sunscreen, dispersion medium and dispersant in physical sunscreen slurry, and using a combined process of homogenizer and bead mill, circulating grinding treatment is carried out to control the grinding temperature and grinding media, the agglomeration of sunscreen particles is significantly reduced.

Benefits of technology

The high dispersion, long-term stability and low viscosity of the physical sunscreen slurry are achieved, which significantly reduces the whiteness, improves the sunscreen index and transparency of the sunscreen products, and improves the skin feeling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119745704A_ABST
    Figure CN119745704A_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of cosmetic technology, and discloses a physical sunscreen slurry and its preparation method and application. The physical sunscreen slurry includes 30 to 60 parts of a physical sunscreen, 23 to 68 parts of a dispersion medium and 3 to 14 parts of a dispersant. The physical sunscreen is titanium dioxide and / or zinc oxide. The dispersion medium is grease. The dispersant is one or more of polyglycerol-3 polydimethylsilylhydroxyethyl polydimethylsiloxane, lauryl polyglycerol-3 polydimethylsiloxyethyl polydimethylsiloxane, PEG-10 polydimethylsiloxane or polyhydroxystearic acid. Among them, the mass ratio of the physical sunscreen to the dispersant is (4.2 to 10): 1. The preparation process of the physical sunscreen slurry of the present invention is simple, and the grinding treatment can improve the dispersibility and long-term stability of the slurry, and reduce the whiteness. At the same time, the slurry has low viscosity and strong fluidity, which is convenient for production operation. The sunscreen product prepared by the physical sunscreen slurry of the present invention has a higher sun protection index and transparency, and the skin feels light and non-greasy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cosmetics, and in particular relates to a physical sunscreen slurry and a preparation method and application thereof. Background Art

[0002] Physical sunscreens have excellent ultraviolet absorption and scattering capabilities and are highly safe for the human body, so they are widely used in the field of cosmetics. Titanium dioxide and zinc oxide particles, as commonly used physical sunscreens, are often used directly in solid form in the production of sunscreen products. This method of use is inconvenient to disperse, and there is a risk of particle agglomeration and reduced sun protection value. At the same time, it may also cause dust pollution to the production workshop. Pre-preparing the physical sunscreen into a sunscreen slurry is not only convenient for production and feeding, but also can improve the sunscreen effect of the product. However, in the process of preparing the sunscreen slurry, due to the lipophilicity and high surface energy of titanium dioxide and zinc oxide, when the content is high, they are prone to irreversible agglomeration in the oil phase, resulting in poor dispersibility and stability of the sunscreen slurry, which directly affects the sunscreen effect, and at the same time, there will be a false white phenomenon that consumers find difficult to accept. Even if the sunscreen slurry initially achieves a good dispersion effect, how to ensure that no agglomeration and precipitation occur during subsequent storage and use, and to maintain a long-term stable dispersion state is a major challenge.

[0003] During the preparation of physical slurry, a homogenizer is usually used to homogenize the pre-treated slurry to disperse the materials. However, high-content titanium dioxide and zinc oxide generally have higher viscosity under the homogenization process, and are prone to agglomeration and sedimentation, and uneven dispersion, which leads to unstable batches and inconvenience in production and use. At the same time, agglomeration also causes reduced sunscreen efficiency and increased whiteness.

[0004] Chinese patent CN116059132B discloses a physical sunscreen and a slurry containing the physical sunscreen. The stability and dispersibility of the slurry are limited to inorganic powders obtained by specific surface treatment agents (HDI / trimethylol hexyl lactone cross-linked polymer, triethoxyoctylsilane), and the application is relatively limited. The material sunscreen slurry limits the median particle size range of the physical sunscreen to 150-300nm, and a stable sunscreen slurry is obtained. However, for physical sunscreens with a particle size of less than 100nm, the particle surface energy is higher, the charge value is larger, and the agglomeration is more serious. Therefore, the agglomeration problem of small-sized physical sunscreens needs to be solved urgently.

[0005] Therefore, it is of great application value to develop a physical sunscreen slurry with high dispersibility, high sun protection index and long-term stability, and to prepare a physical sunscreen product with excellent skin feel and sun protection effect. Summary of the invention

[0006] In response to the above technical problems, the present invention provides a physical sunscreen slurry and a preparation method and application thereof. The prepared slurry has low viscosity, excellent dispersibility and long-term stability, and significantly reduces whiteness. The sunscreen products prepared using the slurry have a high sun protection index and improve the whiteness and skin feel of the sunscreen products.

[0007] The first aspect of the present invention provides a physical sunscreen slurry, comprising the following components in parts by weight:

[0008] Physical sunscreen, 30-60 parts;

[0009] Dispersion medium, 23-68 parts;

[0010] Dispersant, 3 to 14 parts.

[0011] Preferably, the physical sunscreen is titanium dioxide and / or zinc oxide. More preferably, the titanium dioxide is titanium dioxide with a hydrophobic surface treatment, and the zinc oxide is zinc oxide with a hydrophobic surface treatment.

[0012] Preferably, the mass ratio of physical sunscreen agent to dispersant is (4.2-10):1.

[0013] Preferably, the dispersion medium is one or more of C12-15 alcohol benzoate, caprylic / capric triglyceride, pentaerythritol stearate / caprate / caprylate / adipate, isononyl isononanoate, dibutyl adipate, cyclopentasiloxane, polydimethylsiloxane, diphenylsiloxyphenyl trimethylsiloxane or isododecane. More preferably, the viscosity of polydimethylsiloxane is 0.65 cSt to 100 cSt.

[0014] Preferably, the dispersant is one or more of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane, lauryl polyglyceryl-3 polydimethylsiloxyethyl polydimethylsiloxane, PEG-10 polydimethylsiloxane or polyhydroxystearic acid.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned physical sunscreen slurry, the method comprising the following steps:

[0016] Step S1: weighing a physical sunscreen agent, a dispersion medium, and a dispersant according to a predetermined weight ratio, adding the components into a homogenizer, and homogenizing and mixing them uniformly to obtain a pre-dispersed physical sunscreen agent slurry;

[0017] Step S2: placing the pre-dispersed physical sunscreen slurry in a bead mill, subjecting it to a cyclic grinding process, controlling the grinding temperature to be between 20° C. and 45° C., and filtering it through a filter screen to finally obtain a physical sunscreen slurry.

[0018] Preferably, in step S2, during the cyclic grinding process, the grinding medium used is zirconium oxide with a diameter of 20 μm to 500 μm; the linear speed of the bead mill rotor is 1.6 m / s to 15 m / s, and the filling rate of zirconium oxide beads in the bead mill is 50% to 90%.

[0019] The viscosity of the physical sunscreen slurry prepared by the present invention is less than 1000 mPa·s.

[0020] A third aspect of the present invention provides a use of a physical sunscreen slurry in a sunscreen product.

[0021] Compared with the prior art, the present invention has at least the following beneficial effects:

[0022] 1. In the physical sunscreen slurry of the present invention, the physical sunscreen and the dispersant are in a specific mass ratio, and the electrostatic repulsion is used to prevent the sunscreen particles from being adsorbed and agglomerated. After the grinding treatment, the agglomerates of the sunscreen in the physical sunscreen slurry are broken, which can effectively reduce the agglomeration of particles, so that the physical sunscreen slurry of the present invention has excellent dispersibility and long-term stability. On the one hand, it shows the characteristics of low viscosity and strong fluidity, which is convenient for production operation, and on the other hand, the whiteness of the slurry is significantly reduced.

[0023] 2. The sunscreen product prepared by the physical sunscreen slurry of the present invention helps the sunscreen to form a uniform and dense protective layer on the skin, thereby improving the sunscreen effect. Compared with the sunscreen product prepared by the conventional homogeneous slurry, the sunscreen product prepared by the physical sunscreen slurry of the present invention has a higher sun protection index and transparency, and feels light and non-greasy on the skin. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a particle size distribution diagram of the physical sunscreen slurry in Example 2;

[0025] Figure 2 The microscope images and SEM images of the physical sunscreen slurry in Example 1 and Comparative Example 2;

[0026] Figure 3 The whiteness comparison diagram of the physical sunscreen slurry coated on cardboard and the back of the hand in Example 1, Example 2, Example 3 and Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4;

[0027] Figure 4 It is a comparison chart of the whiteness of the sunscreen lotions prepared in Application Example 1, Application Example 2, Example 3 and Application Comparative Example 1, Application Comparative Example 2, and Application Comparative Example 3 applied on cardboard and the back of the hand. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0029] Unless otherwise specified, the raw materials and materials used in the examples of the present invention are purchased through general commercial channels.

[0030] In the following examples and comparative examples, the raw materials used are all commercially available products, and the sources of the raw materials are as follows (only the functional ingredients are reflected, and other necessary auxiliary ingredients are not repeated):

[0031] Titanium dioxide with hydrophobic surface treatment (hereinafter referred to as titanium dioxide), trade name UNI-TO-AL11SA, average particle size 15-60nm;

[0032] Surface hydrophobic treated zinc oxide (hereinafter referred to as zinc oxide), trade name NAOCOS ZS1004B, average particle size 20-50 nm;

[0033] Cyclopentasiloxane, trade name KF-995;

[0034] 1.5cSt polydimethylsiloxane, trade name MIRASIL DM 1.5;

[0035] 2cSt polydimethylsiloxane, trade name KF-96L-2CS;

[0036] 6cSt polydimethylsiloxane, trade name KF-96A-6T;

[0037] Isononyl isononanoate, trade name RADIA 7710;

[0038] Pentaerythritol stearate / caprate / caprylate / adipate, trade name

[0039] Schercemol TM CATC CN ester;

[0040] Polyglyceryl-3 polydimethylsiloxyethyl dimethicone, trade name KF-6106;

[0041] Lauryl Polyglyceryl-3 Polydimethylsiloxyethyl Dimethicone, trade name KF-6115;

[0042] PEG-9 polydimethylsiloxyethyl dimethicone, trade name KF-6028;

[0043] Disteardimethylammonium hectorite, trade name BENTONE 38VCG.

[0044] <Example 1>

[0045] This embodiment discloses a physical sunscreen slurry, comprising the following components in parts by weight:

[0046] 17.86 parts of titanium dioxide, 32.14 parts of zinc oxide, 45 parts of cyclopentasiloxane, and 5 parts of polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone.

[0047] This embodiment also discloses a method for preparing the physical sunscreen slurry, which comprises the following steps:

[0048] S1: Weigh titanium dioxide, zinc oxide, cyclopentasiloxane, and polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane according to the above weight proportions, add them into a homogenizer, and mix them uniformly to obtain a pre-dispersed physical sunscreen slurry;

[0049] S2: The pre-dispersed physical sunscreen slurry is then placed in a bead mill, subjected to a cyclic grinding process, the grinding temperature is controlled between 20 and 45° C., and filtered through a filter to finally obtain a physical sunscreen slurry.

[0050] In S2, the cyclic grinding process uses zirconium oxide with a diameter of 50 μm as the grinding medium, a grinding speed of 12 m / s, and a zirconium oxide bead filling rate of 60%.

[0051] The viscosity of a physical sunscreen slurry is 806.7 mPa·s.

[0052] <Example 2>

[0053] This embodiment discloses a physical sunscreen slurry, comprising the following components in parts by weight:

[0054] 15 parts of titanium dioxide, 27 parts of zinc oxide, 15 parts of 1.5 cSt polydimethylsiloxane, 30 parts of 2 cSt polydimethylsiloxane, 3 parts of isononyl isononanoate, and 10 parts of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane.

[0055] This embodiment also discloses a method for preparing the physical sunscreen slurry, which comprises the following steps:

[0056] S1: Weigh titanium dioxide, zinc oxide, polydimethylsiloxane, 2cSt polydimethylsiloxane, isononyl isononanoate, and polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane according to the above weight parts, add them into a homogenizer and mix them evenly to obtain a pre-dispersed physical sunscreen slurry;

[0057] S2: The pre-dispersed physical sunscreen slurry is then placed in a bead mill, subjected to a cyclic grinding process, the grinding temperature is controlled between 20° C. and 45° C., and filtered through a filter to finally obtain a physical sunscreen slurry.

[0058] In S2, the cyclic grinding process uses zirconium oxide with a diameter of 200 μm as the grinding medium, a grinding speed of 11 m / s, and a zirconium oxide bead filling rate of 85%.

[0059] The viscosity of a physical sunscreen slurry is 345.3 mPa·s.

[0060] <Example 3>

[0061] This embodiment discloses a physical sunscreen slurry, comprising the following components in parts by weight:

[0062] 15 parts of titanium dioxide, 27 parts of zinc oxide, 30 parts of 6cSt polydimethicone, 20 parts of isononyl isononanoate, 2 parts of pentaerythrityl stearate / caprate / caprylate / adipate, 6 parts of lauryl polyglyceryl-3 polydimethylsiloxyethyl polydimethicone.

[0063] This embodiment also discloses a method for preparing the physical sunscreen slurry, which comprises the following steps:

[0064] S1: Weigh titanium dioxide, zinc oxide, 6cSt polydimethylsiloxane, isononyl isononanoate, pentaerythrityl stearate / caprate / caprylate / adipate, and lauryl polyglyceryl-3 polydimethylsiloxyethyl polydimethylsiloxane according to the above weight parts, add them into a homogenizer and mix them evenly to obtain a pre-dispersed physical sunscreen slurry;

[0065] S2: The pre-dispersed physical sunscreen slurry is then placed in a bead mill, subjected to a cyclic grinding process, the grinding temperature is controlled between 20° C. and 45° C., and filtered through a filter to finally obtain a physical sunscreen slurry.

[0066] In S2, the cyclic grinding process uses zirconium oxide with a diameter of 200 μm as the grinding medium, a grinding speed of 11 m / s, and a filling rate of zirconia beads of 85%.

[0067] The viscosity of a physical sunscreen slurry is 587.7 mPa·s.

[0068] <Comparative Example 1>

[0069] A physical sunscreen slurry, which differs from Example 1 in that it comprises the following components in parts by weight:

[0070] 17.86 parts of titanium dioxide, 32.14 parts of zinc oxide, 48.5 parts of cyclopentasiloxane, and 1.5 parts of polyglyceryl-3 polydimethylsilyl hydroxyethyl dimethicone.

[0071] The preparation method of the physical sunscreen slurry is exactly the same as that of Example 1. After testing, the viscosity of the physical sunscreen slurry is 2253 mPa·s.

[0072] <Comparative Example 2>

[0073] A physical sunscreen slurry, the components of which are exactly the same as those in Example 1.

[0074] The preparation method of the physical sunscreen slurry is different from that of Example 1 in that the physical sunscreen slurry is not subjected to the S2 process. According to the test, the viscosity of the physical sunscreen slurry is 1523 mPa·s.

[0075] <Comparative Example 3>

[0076] A physical sunscreen slurry, the components of which are exactly the same as those in Example 1.

[0077] The preparation method of the physical sunscreen slurry is different from that of Example 1 in that the grinding medium used is zirconium oxide with a diameter of 1 mm. According to the test, the viscosity of the physical sunscreen slurry is 1266 mPa·s.

[0078] <Comparative Example 4>

[0079] A physical sunscreen slurry, which differs from Example 2 in that it comprises the following components in parts by weight:

[0080] 15 parts of titanium dioxide, 27 parts of zinc oxide, 15 parts of 1.5 cSt polydimethylsiloxane, 26 parts of 2 cSt polydimethylsiloxane, 3 parts of isononyl isononanoate, and 14 parts of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane.

[0081] The preparation method of the physical sunscreen slurry is exactly the same as that of Example 2. After testing, the viscosity of the physical sunscreen slurry is 423.7 mPa·s.

[0082] The slurries prepared in Examples 1, 2, 3 and Comparative Examples 1, 2, 3, 4 were subjected to the following tests under the same conditions, including viscosity test, dispersibility test, stability test, whiteness test of physical sunscreen slurry, and dispersibility test, whiteness test, machine test, human sunscreen test, sensory test, etc. of sunscreen products.

[0083] <Test Example 1>

[0084] Viscosity and stability test of physical sunscreen slurry

[0085] The viscosity test was performed using the following method: DV2TTM LV viscometer, at 25°C, using LV62 or LV63 spindle, 30 rpm test sample viscosity, the results are shown in Table 1.

[0086] The specific operations of the stability test are:

[0087] The physical sunscreen slurry was placed in a constant temperature and humidity incubator at 25°C and 49°C for 90 days to observe its stability. The physical sunscreen slurry was allowed to stand at room temperature for 24 hours, and then centrifuged at 3000 rpm and a constant temperature of 25°C for 10 minutes to observe its stability. The results are shown in Table 1.

[0088] Table 1. Viscosity and stability results

[0089]

[0090] According to the data in Table 1, Examples 1 to 3 are stable for a long time at 25°C and 49°C without stratification, and there is no sedimentation after centrifugation, indicating that when the mass ratio of the physical sunscreen agent to the dispersant satisfies (4.2 to 10): 1, the physical sunscreen agent is better dispersed in the dispersion medium, the slurry is stable, and it is convenient for production operation and batch stability. The particles in the slurries prepared in Comparative Examples 1 to 3 agglomerated, and none of them passed the stability test, and oiling and centrifugal sedimentation occurred, and their viscosities were all higher than 1000mPa·s. Although the slurry prepared in Comparative Example 4 did not stratify after centrifugation, it showed slight sedimentation after long-term placement.

[0091] From the comparison between Examples 1 to 3 and Comparative Example 1, it can be seen that when the mass ratio of the physical sunscreen agent to the dispersant is in the range of (4.2 to 10):1, the dispersant adheres to the surface of the sunscreen agent particles, so that the charge density on the particle surface increases, and the electrostatic repulsion between the particles makes the sunscreen agent particles uniformly dispersed and not aggregated, and the slurry is stable. When the mass ratio of the physical sunscreen agent to the dispersant is greater than 10:1, that is, the dispersant polyglycerol-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane is too little, the electrostatic repulsion on the particle surface is insufficient, causing the sunscreen agent particles in the slurry to agglomerate, which is intuitively manifested as high viscosity, centrifugal sedimentation and long-term instability.

[0092] By comparing Examples 1 to 3 and Comparative Example 4, it can be seen that when the mass ratio of physical sunscreen and dispersant is less than 4.2:1, that is, the dispersant polyglycerol-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane is too much, the slurry is centrifuged without stratification, and the immediate dispersion effect is good. However, during long-term placement, the sunscreen particles and the excess dispersant molecules are constantly moving, and overlapping areas are generated when the particles are close, so that the entropy of the excess dispersant molecules increases, the free energy of the system decreases, and an emptying effect is generated, resulting in the aggregation of sunscreen particles and the sedimentation of the slurry. In addition, excessive dispersant will cause the slurry to feel greasy and heavy on the skin, and increase production costs.

[0093] From the comparison between Example 1 and Comparative Example 2, it can be seen that the slurry treated by the homogenization process in Comparative Example 2 has poor dispersibility and stability, rapid stratification and centrifugal sedimentation occur, and the viscosity of the slurry is high, indicating that the titanium dioxide and zinc oxide particles are agglomerated;

[0094] From the comparison between Example 1 and Comparative Example 3, it can be seen that in Comparative Example 3, zirconia beads with a diameter of 1 mm are used for grinding, and the slurry also agglomerates and settles. This is because the larger the diameter of the zirconia beads, the larger the pores between the zirconia beads, resulting in low grinding efficiency; while the physical sunscreen slurry in Example 1 is treated with a suitable grinding process and has good stability.

[0095] By comparing Example 2 with Comparative Examples 2 and 3, it can be seen that when the mass ratio of the physical sunscreen agent to the dispersant satisfies (4.2-10):1, but without the grinding process or when the diameter of the zirconia beads is different, the prepared slurry still exhibits unstable phenomena such as particle agglomeration, sedimentation or stratification.

[0096] <Test Example 2>

[0097] Dispersion test of physical sunscreen slurry

[0098] (1) The slurries prepared in Examples 1 and 2 and Comparative Examples 1-3 were analyzed for particle size using a nanoparticle size analyzer. The results are shown in Table 2. The particle size distribution of the physical sunscreen slurry in Example 2 is shown in Table 2. Figure 1 ) as a typical example.

[0099] Table 2. Particle size distribution

[0100] D10 / nm D50 / nm D90 / nm Average particle size / nm Example 1 112.4 230.1 470.9 269.1 Example 2 114.2 218.4 398.1 232.4 Example 3 112.1 229.5 461.7 265.8 Comparative Example 1 501.48 960.94 1841.33 960.94 Comparative Example 2 173.1 405.5 953.6 506.4 Comparative Example 3 169.2 386.0 834.7 462.8 Comparative Example 4 120.1 221.1 428.4 252.7

[0101] According to the particle size distribution in Table 2, the particle sizes of Examples 1 to 3 are small and narrowly distributed, indicating that when the mass ratio of the physical sunscreen agent to the dispersant is in the range of (4.2 to 10):1, the dispersion of the sunscreen agent particles is better. The particle size distributions of Comparative Example 4 and Example 2 are similar, indicating that when the mass ratio of the physical sunscreen agent to the dispersant reaches 4.2:1, if the dispersant ratio is further increased, the particle size and dispersibility of the slurry will not be further improved. The particle sizes of Comparative Examples 1 to 3 are all large and widely distributed, indicating the presence of large particles or particle agglomeration.

[0102] (2) The morphology of the slurries prepared in Example 1 and Comparative Example 2 was observed using a Lecia DM2700 M optical microscope at a magnification of 200 times. Figure 2 a, as shown in 2b.

[0103] (3) A FEI Nano450 scanning electron microscope (SEM) was used to observe the microscopic morphology of the slurries prepared in Example 1 and Comparative Example 2. The experimental method was as follows: the sample was dropped onto the conductive glue, and then sprayed with gold for testing after drying. The acceleration voltage was set to 20 KV, the working distance was 4.7 mm, and the observation was performed at a magnification of 80,000 times.

[0104] The scanning electron microscope images of the slurry prepared in Example 1 and Comparative Example 2 are as follows: Figure 2 c, as shown in 2d.

[0105] according to Figure 2 From the microscope and SEM images, it can be seen that the particles of Example 1 have good dispersibility, while the particles of Comparative Example 2 have adhesion and agglomeration, which indicates that the grinding process can improve agglomeration and has better dispersibility than the homogenization process.

[0106] <Test Example 3>

[0107] Whiteness test of physical sunscreen paste

[0108] (1) Drop the physical sunscreen slurry on the cardboard, use the automatic coating machine to push the 30μm applicator to apply, and observe the whiteness and fineness of the sample. (2) Drop 0.1g of the physical sunscreen slurry on the back of the hand, apply it evenly in a circular motion for 30 seconds, and observe the whiteness of the sample. The results are shown in Figure 3 .

[0109] according to Figure 3 It can be seen that the whiteness from high to low is Comparative Example 1, Comparative Example 2, Comparative Example 3, Example 1, Example 3, Comparative Example 4, and Example 2. This shows that the whiteness of the physical sunscreen slurry is related to the dispersibility of its physical sunscreen particles. When the dispersibility is better and the particle size is smaller, the specific surface area of ​​the particles is larger, so the scattering effect is weakened, and it is not easy to appear white when applied. The whiteness of Comparative Example 4 and Example 2 is similar, indicating that when the mass ratio of physical sunscreen to dispersant reaches 4.2:1, if the dispersant ratio continues to increase, the whiteness of the slurry will not decrease.

[0110] <Test Example 4>

[0111] Whiteness test of sunscreen products

[0112] According to the formula in Table 3, sunscreen products were prepared using the physical sunscreen slurries of Example 1, Example 2, Comparative Example 1, Comparative Example 2, and Comparative Example 4, respectively, and were marked as Application Example 1, Application Example 2, Application Comparative Example 1, Application Comparative Example 2, and Application Comparative Example 3. The sunscreen products were all water-in-oil emulsions, and the other components were the same except for the physical sunscreen slurry. The preparation method of the sunscreen product is as follows: (1) homogenizing and dispersing the raw materials of phase A; (2) stirring and dissolving the raw materials of phase B; (3) slowly adding the raw materials of phase B to the raw materials of phase A, homogenizing and mixing, and obtaining a physical sunscreen emulsion.

[0113] The whiteness test method of sunscreen products is as follows: (1) Drop the sunscreen product on cardboard, use an automatic coating machine to push a 30μm applicator to apply, and observe the whiteness and fineness of the sample. (2) Drop 0.1g of sunscreen product on the back of the hand, apply it evenly in a circular motion for 30 seconds, and observe the whiteness of the sample. The results are shown in Figure 4 .

[0114] Table 3. Sunscreen product formula

[0115]

[0116]

[0117] Note: In Table 3, the percentages of each component in the application examples and comparative examples are all weight percentages.

[0118] according to Figure 4 It can be seen that the sunscreen lotions prepared in Application Examples 1 and 2 have fine materials, are transparent and bluish after spreading, and have a low degree of whitening. The whiteness of Application Example 1 and Application Comparative Example 3 is similar after application. The sunscreen lotions prepared in Application Comparative Examples 1 and 2 appear white during application. This result also reflects the difference in the dispersion of physical sunscreen slurry in sunscreen products.

[0119] <Test Example 5>

[0120] Machine testing and human sun protection testing of sunscreen products

[0121] (1) SPF machine test: refer to the standard in vitro test method of Colipa 2011, taking 1.3 mg / cm 2 The test sample is evenly applied on the PMMA board, dried in the dark room for 15 minutes, and then measured using a UV 2000s sun protection factor analyzer. (2) SPF human body test: Refer to the human body method test in the "Cosmetic Safety Technical Specifications" and use a sun protection index tester to measure the SPF value of the product. The larger the SPF value, the better the sun protection effect.

[0122] Table 4. SPF values ​​of sunscreen products measured by machine

[0123] Average SPF value measured by machine Application Example 2 54.43 Application Comparative Example 1 35.65

[0124] According to the data in Table 4, although the physical sunscreen slurries used in Application Example 2 and Application Comparative Example 1 are both processed by the grinding process within the scope of the present invention, the mass ratio of the physical sunscreen to the dispersant in Application Comparative Example 1 is lower than 4.2:1, and the agglomeration of the sunscreen particles causes the sunscreen value of the sunscreen product to be low; while the mass ratio of the physical sunscreen to the dispersant in Application Example 2 is higher, which can reduce the agglomeration of the sunscreen particles, improve the absorption and scattering of ultraviolet rays by the sunscreen, and thus enhance the sunscreen effect of the sunscreen product.

[0125] Table 5. SPF human test values ​​of sunscreen products

[0126] Human body SPF value Application Example 1 48 Application Comparative Example 2 37

[0127] According to the data in Table 5, compared with the comparative example 2, the sunscreen lotion prepared in the application example 1 has excellent sunscreen effect, which indicates that the grinding process is helpful for the dispersion of the physical sunscreen slurry in the sunscreen product, and the sunscreen forms a uniform and dense protective layer on the skin, thereby improving the sunscreen value.

[0128] <Test Example 6>

[0129] Sensory testing of sunscreen products

[0130] Sensory evaluation was performed on the sunscreen lotions prepared in Example 1 and Comparative Example 2. 19 sensory evaluators were selected to evaluate the two test products from three dimensions: during facial application, after film formation, and overall preference, by means of paired comparison.

[0131] Table 6. Sensory comparison of sunscreen products

[0132]

[0133] Note 1: ** indicates significant difference at 1% significance level

[0134] According to the data in Table 6, the sunscreen lotion prepared in Example 1 is fine, has good spreadability, and has a light and breathable skin feel. Compared with Comparative Example 2, there is no obvious whitening feeling after application and film formation. This shows that the physical sunscreen agent in the grinding slurry and the dispersion medium have better dispersibility, and the particles are easier to spread during the application process. Overall, the sunscreen lotion prepared by the physical sunscreen agent slurry provided in Example 1 has a higher overall preference.

[0135] Sensory evaluation was performed on the sunscreen lotions prepared in Example 2 and Comparative Example 3. 17 sensory evaluators were selected to evaluate the two test products from three dimensions: during facial application, after film formation, and overall preference, by means of paired comparison.

[0136] Table 7. Sensory comparison of sunscreen products

[0137]

[0138] Note 1: ** indicates significant difference at 1% significance level

[0139] According to the data in Table 7, the whitening degree of the sunscreen lotions prepared in Application Example 2 and Comparative Example 3 is similar. The skin feel of Application Example 2 after film formation is drier, less sticky, fresher and less greasy, while in Comparative Example 3, due to the higher mass ratio of the dispersant, a noticeable stickiness and greasy feeling is caused.

[0140] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A physical sunscreen slurry, characterized in that: By weight, it includes the following components: Physical sunscreen, 30-60 parts; Dispersion medium, 23-68 parts; Dispersant, 3 to 14 parts; Wherein, the mass ratio of the physical sunscreen to the dispersant is (4.2-10):1, The physical sunscreen is titanium dioxide and / or zinc oxide; The dispersion medium is grease; The dispersant is one or more of polyglyceryl-3 polydimethylsilyl hydroxyethyl polydimethylsiloxane, lauryl polyglyceryl-3 polydimethylsiloxyethyl polydimethylsiloxane, PEG-10 polydimethylsiloxane or polyhydroxystearic acid.

2. The physical sunscreen slurry according to claim 1, characterized in that The titanium dioxide is titanium dioxide with a hydrophobic surface treatment.

3. The physical sunscreen slurry according to claim 1, characterized in that: The zinc oxide is zinc oxide with a surface hydrophobic treatment.

4. The physical sunscreen slurry according to claim 1, characterized in that: The oil is C12-15 alcohol benzoate, caprylic / capric triglyceride, pentaerythritol stearate / caprate / caprylate / adipate, isononyl isononanoate 、 One or more of dibutyl adipate, cyclopentasiloxane, polydimethylsiloxane, diphenylsiloxyphenyl trimethylsiloxane or isododecane.

5. The physical sunscreen slurry according to claim 4, characterized in that: The viscosity of the polydimethylsiloxane is 0.65 cSt to 100 cSt.

6. The method for preparing the physical sunscreen slurry according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step S1: weighing the physical sunscreen agent, dispersion medium, and dispersant according to a predetermined weight ratio, adding them into a homogenizer and homogenizing and mixing them evenly to obtain a pre-dispersed physical sunscreen agent slurry; Step S2: placing the pre-dispersed physical sunscreen slurry in a bead mill, subjecting it to a cyclic grinding process, controlling the grinding temperature to be between 20° C. and 45° C., and filtering it through a filter screen to finally obtain a physical sunscreen slurry; Wherein, in step S2, during the cyclic grinding process, the grinding medium used is zirconium oxide with a diameter of 20 μm to 500 μm.

7. The method for preparing the physical sunscreen slurry according to claim 6, characterized in that: In step S2, the linear speed of the bead mill rotor is 1.6 m / s to 15 m / s.

8. The method for preparing the physical sunscreen slurry according to claim 6, characterized in that: In step S2, the filling rate of the zirconia beads in the bead mill is 50% to 90%.

9. The method for preparing the physical sunscreen slurry according to claim 6, characterized in that: The viscosity of the physical sunscreen slurry is less than 1000 mPa·s.

10. Use of the physical sunscreen slurry according to any one of claims 1 to 5 in sunscreen products.

Citation Information

Patent Citations

  • Physical sunscreen agents and their preparation methods, and slurries containing physical sunscreen agents and their preparation methods.

    CN116059132B

Cited By

  • Two-phase powder slurry composition, application thereof, oil-in-water sunscreen system and preparation method of oil-in-water sunscreen system

    CN122005318A

  • Two-phase powder paste composition and its application, water-in-oil sunscreen system and its preparation method

    CN122005318B

  • Base Composition for Ultraviolet Protection Containing Titanium Dioxide Complex of Different Particle Sizes and Cosmetic Sunscreen Composition Comprising the Same

    KR102998004B1